2011
DOI: 10.1007/s10900-011-9521-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Time of Start of Prenatal Care and Number of Prenatal Care Visits During Pregnancy Among Nepalese Women

Abstract: This study is aimed at investigating the factors determining the timing of first prenatal care (PNC) visit and the number of PNC visits among a national representative sample of Nepali women. Data was drawn from the 2006 Nepal Demographic and Health Survey on women age 15-49 years old who had delivery within three years prior to the survey (N = 4,136). Multinomial logistic regression was used to study the association between socio-demographic variables and two outcome variables--the timing of first PNC and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
57
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 27 publications
(28 reference statements)
16
57
0
3
Order By: Relevance
“…However, this association lost statistical significance when we controlled for local level variables. Similar results were found in a study carried out in Nepal when controlling for sociodemographic characteristics 44 . In other studies conducted in Colombia, being employed was not a significant determinant of receiving antenatal care 12 .…”
Section: Colombian Demographic and Health Survey (N = 12373)supporting
confidence: 88%
See 1 more Smart Citation
“…However, this association lost statistical significance when we controlled for local level variables. Similar results were found in a study carried out in Nepal when controlling for sociodemographic characteristics 44 . In other studies conducted in Colombia, being employed was not a significant determinant of receiving antenatal care 12 .…”
Section: Colombian Demographic and Health Survey (N = 12373)supporting
confidence: 88%
“…Authors have found a strong association between household poverty 18 or neighborhood poverty 22 and a lower likelihood of accessing antenatal care in rural areas in Mali and Haiti. In other countries, studies revealed that mothers were less likely to receive visits or complete the minimum number of visits in rural areas 44,45 .…”
Section: Colombian Demographic and Health Survey (N = 12373)mentioning
confidence: 99%
“…They have also been shown to increase rates of immunisation; enhance the chances of initiating breastfeeding within one hour of birth and the maintenance of exclusive breastfeeding for more than four months [27]; and increase the use of postnatal check-ups [29,30]. An Indian study found that, compared to women who had neonatal deaths, those with a live birth had received better quality ANC which included body weight measurement, blood and urine testing, a full course of iron tablets, tetanus toxoid injections, abdominal examination and ultrasonography [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nepal'de yapılan bir çalışmada gebelerin %28'i, Çatak B. ve ark. | Doğum öncesi bakım hizmetlerinin sahada izlemi ve değerlendirilmesi: Bursa örneği Nijerya'da yapılan bir çalışmada %44'ü ve Zambiya'da ise %2'si hiç DÖB almamıştır [6][7][8] . Ülkemizde yapılan benzer saha çalışmalarından Burdur'da gebelerin tamamı en az bir kez DÖB almış iken, Adıyaman'da yapılan çalışmada gebelerin %1,7'sinin, İstanbul'da yapılan çalışmada %0,6'sının aile hekimi ve/veya kadın hastalıkları ve doğum uzmanından DÖB almadığı gösterilmiştir [9][10][11] .…”
Section: Discussionunclassified
“…Araştırmada 14 haftadan küçük gebelerin tamamı ilk doğum öncesi bakımını aile hekiminden almış iken, 33 hafta üzeri gebeler ve doğum yapmış annelerin %81,1'i ilk doğum öncesi bakımını 14 hafta içinde almıştır. Nepal'da yapılan çalışmada gebelerin yaklaşık yarısının gebelikten 3 ay sonra DÖB aldığı bildirilmektedir [6] . İstanbul'da doğum yapmış gebelerin %57,1'i, Karabük'te %84,3'ü ilk doğum öncesi bakımını ilk 14 hafta içinde almıştır (11,13) .…”
Section: Discussionunclassified